The plant cytoskeleton in cell differentiation and development - Hussey, Patrick J (Blackwell, 2012)
A timely review of this rapidly expanding field which capitalises on the wealth of information generated by post-genomic technologies * Broad coverage of the plant cytoskeleton, set in the context of plant development * Thoroughly referenced and so represents a point of access to the detailed literature.